2019
DOI: 10.1249/jsr.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Management of Rotator Cuff Injuries in the Master Athlete

Abstract: Rotator cuff (RTC) injuries are common in master athletes, especially overhead athletes. Risk factors include aging and degeneration as nonmodifiable and volume of activity, muscle weakness, and loss of motion as modifiable. The clinical presentation involves limited range of motion (ROM), pain at rest and at night. Injury classification into traumatic versus nontraumatic and tendinopathy, partial or full-thickness tears helps to establish a treatment plan. RTC injury rehabilitation protocols are criteria-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…In recent years, with the development of muscle physiology, it has been found that rotator cuff injuries are usually accompanied by various muscle changes, including atrophy, fibrosis and fatty infiltration, which can have a significant impact on the mechanical and biological properties of tendons. 33,34 The degree of fat infiltration is also closely related to postoperative rehabilitation and re-tear injury, and also has a significant impact on muscle atrophy and contractility.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of muscle physiology, it has been found that rotator cuff injuries are usually accompanied by various muscle changes, including atrophy, fibrosis and fatty infiltration, which can have a significant impact on the mechanical and biological properties of tendons. 33,34 The degree of fat infiltration is also closely related to postoperative rehabilitation and re-tear injury, and also has a significant impact on muscle atrophy and contractility.…”
Section: Discussionmentioning
confidence: 99%
“…The exercise was divided into simple ROM exercises and therapeutic exercises, and the intensity of the exercise was tailored to the healing process [11]. For continuous passive motion (CPM) during ROM exercise, ARTUS-703S (Eugene Medicare, Seoul, Korea) was used to maintain mobility [23]. Therapeutic exercises focused on conscious exercise for scapular dyskinesis.…”
Section: Exercisementioning
confidence: 99%
“…If swelling and pain observed in the movement of rotator cuff muscle so it should passed through R.I.C.E protocols and the rehabilitation process started as it free from pain and immobilization of rotator cuff muscles. The injured athletes of the rotator cuff muscle have been given a proper heed along with organized protocols of rehabilitation plan executed and it was look that safety and prevention from further deterioration of the affected area [17]. The athletes were given proper rehabilitation plan of isometric and isotonic strength exercise, range of motion exercises (flexibility exercises), mobilizing exercises along with theraband exercises (resistance) as per required by researcher, trainer, coaches and doctors [18,19] (Rosa & Robert 2022) [20].…”
Section: Treatment Of Rotator Cuff (Rc) Injuriesmentioning
confidence: 99%